Long Non-coding RNA in Neurons: New Players in Early Response to BDNF Stimulation - Aliperti, Vincenza; Donizetti, Aldo (Frontiers in Molecular Neuroscience, 2016)
Brain-derived neurotrophic factor (BDNF) is a neurotrophin family member that is highly expressed and widely distributed in the brain. BDNF is critical for neural survival and plasticity both during development and in adulthood, and dysfunction in its signaling may contribute to a number of neurodegenerative disorders. Deep understanding of the BDNF-activated molecular cascade may thus help to find new biomarkers and therapeutic targets. One interesting direction is related to the early phase of BDNF-dependent gene expression regulation, which is responsible for the activation of selective gene programs that lead to stable functional and structural remodeling of neurons. Immediate-early coding genes activated by BDNF are under investigation, but the involvement of the non-coding RNAs is largely unexplored, especially the long non-coding RNAs (lncRNAs). lncRNAs are emerging as key regulators that can orchestrate different aspects of nervous system development, homeostasis, and plasticity, making them attractive candidate markers and therapeutic targets for brain diseases. We used microarray technology to identify differentially expressed lncRNAs in the immediate response phase of BDNF stimulation in a neuronal cell model. Our observations on the putative functional role of lncRNAs provide clues to their involvement as master regulators of gene expression cascade triggered by BDNF.